Effects of 11-ketotestosterone on genital papilla morphology in the sex changing fish Lythrypnus dalli - Carlisle, S. L. (2012)
Five days after implantation with 11-ketotestosterone (KT) female Lythrypnus dalli exhibited elevated urinary KT levels and male-like genital papilla morphology. Papilla length increased, width decreased, and length : width ratio increased. Control fish exhibited increases in papilla length, and length : width ratio on day 3, but not on day 5. Changes in the total area of the papilla were not statistically significant. It is suggested that KT mediates genital papilla morphology rapidly and thus may be a useful indicator of circulating KT in L. dalli.